PELAKSANAAN EVALUASI PROGRAM OLEH GURU BK DI SMP NEGERI SE-KECAMATAN KURANJI PADANG - Manasari, Gustia; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This research is motivated by the lack of effetiveness the inplemention evaluation program by counselor teacher in junior high allof regencyKuranji Padang school. So that, the researcher interested to do the research. Based on the first sorvey, the researcher found that the counselor teacher not well yet to done implementation and seen how the implementation of evaluation program. This research aims to describe, 1). Preparation of evaluation program, 2).Instrument that used, 3).Implementation of evaluation program.                                              This research is descriptive qualitative study. Sample of the research are all of counselor teachers at junior hingh schoolin all of reggencyesKuranji Padang data were collected through interview and documentation study to implementation evaluation program. The data analysis technigveused is reduction data, describe the data, and eoncluded the data. The resuit of the research found that, 1). The tack of prepation of evaluation program, 2).Instrumet that used not well yet, 3). The lack of implementation activity evaluation program that done by all of counselor teachers. Basedonresuit of the research, nish that all of conunselor teachers inrease implementation evaluation program with effectiveness and efficient.